CARBONATE MOUND DEVELOPMENT AT THE SW ROCKALL TROUGH MARGIN BASED ON HIGH RESOLUTION TOBI AND SEISMIC RECORDING - Mienis F.; van Weering T.; de Haas H.; de Stigter H.; Huvenne V.; Wheeler A. (My University, 2006)
In 2002, high-resolution sidescan sonar images of a mound area at the SW Rockall Trough margin were recorded with the TOBI deep towed sidescan sonar. Processed TOBI images with a pixel resolution of 6 m provide a unique overview of the carbonate mound distribution and related sedimentary features around the mounds. Three morphologically distinct areas can be recognised on the TOBI mosaic. In area I (between 500 and 600 m water depth), upslope of the mounds, giant sediment waves are found with wavelengths up to 500 m, with wave crests of more than 10 km long and with an amplitude of up to 30 m, reflected with a high backscatter on the TOBI image. Area II (between 600 and 1000 m water depth), along the upper margin flank, is characterised by clustered and isolated carbonate mounds, forming elongated ridges with an orientation perpendicular to the slope. Sedimentary structures such as flow ridges, sediment waves, local scouring at the foot of some mounds and draping of sediment around mounds indicate the influence of strong near-bed currents, oriented in two main current directions parallel to the margin, as well as in a similar direction as the mound clusters. The mound clusters are several kilometres long, can be over 380 m high and are dissected by downslope directed channels. On the TOBI image, the mounds appear as regions of high backscatter caused by the presence of cold water coral colonies on the sediment and by distinct shadows. All mounds have their tops at a specific depth level (500-600 m water depth). Area III (between 900 and 1200 m water depth) below the mounds is characterised by disturbed sediments with distinct slump scars and flow ridges. 2D high resolution seismic profiling perpendicular and parallel to the slope across the mounds does in general not reveal strong internal reflectors within the mounds. In contrast, three strong reflectors can be observed in the sedimentary sequence underneath the mounds. The upper reflector C10 (of early Pliocene age) is an erosional unconformity, above which most of the mounds and sediment waves seem to have developed. The second erosional unconformity C20 (of middle Miocene age) is formed by an apparent irregular surface that locally is dissected by some small faults. Reflectors C10 and C20 have been found in two different mound clusters in the mound area, indicating that mound development possibly started after formation of reflector C20. The third reflector forms the acoustic basement, which is locally dissected by some small faults that are located below the mounds. At least two stages of mound formation are recognised on the seismic profiles. © 2006 Elsevier B.V. All rights reserved.
Keywords: CARBONATE MOUNDS; COLD WATER CORALS; HIGH-RESOLUTION SIDESCAN SONAR; SEDIMENT WAVES; SEISMIC PROFILES; TOBI; Pliocene; Miocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен